Abordagem econômica na gestão de resíduos sólidos de igarapés urbanos de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The present research aims to analyze the causes of the generation of solid domestic waste in the municipality of Manaus and its disposal in local urban igarapés - small navigable rivers in the Amazon region -, the composition and the amount of solid waste removed from streams by the respective Municipal Administration as well as to verify the economic instruments that can be used to minimize and reuse waste. It was adopted the multiple case study method, considering the choice of more than one analysis place, its holistic and real-world character, the provision of a wide variety of evidences (documents, photographs, observation sheets and weighings), the possibility of generalizations from different perspectives, among other legitimating factors of the method‟s use. The phenomenon studied is something complex and contemporary, with several group, individual and relational approaches of social, political and economic associated order. The approach strategy used was exploratory and descriptive, or instrumental and exploratory. The waste amounts removed from igarapés in different times of the year make totals in the thousands of tons and cause huge expenses for the public treasure. The problem is an old one, and among the reasons for its continuity are the high generation of waste by each Manaus inhabitant and the low environmental awareness of the population, which has a part that lives and interacts near in the margins of urban watercourses. The results of the survey revealed that there are significant solid waste - 36 kg of PET bottles, 76 kg of soft plastics, 34 kg of hard plastics, 45 kg of paper/paperboard packaging, 10 kg of aluminum cans, 88 kg of other metals, 27 kg of glass, 26 kg of styrofoam, 26 kg of tires, 122 kg of rags, 59 kg of plants, 177 kg of wood and 559 kg of other materials - taken off by Municipal Secretary of Public Cleaning from igarapés of São Raimundo and Educandos. Among the waste present in the local water trash, it was found that there is a considerable range of materials with potential for economic reuse and social inclusion, which can be managed by public policies and the use of economic and environmental valuation tools. The main types of economic instruments adopted in environmental management are environmental taxes – prices to be paid for pollution –, the creation of a market for purchase and sale of pollution rights, subsidies – incentives to stimulate reduction or control costs of emission –, and the system of deposit return.
Economic approach in the management of solid waste from urban rivers of Manaus
Keywords: Resíduos sólidos; Igarapés; Instrumentos econômicos; Políticas públicas; Solid waste; Public policies; Economic instruments; OUTROS